Respuesta :

ali015
Answer this question by plugging each coordinate point into the distance formula, which is used to calculate the distance between two points.

The distance formula is: 
[tex] \text{ Distance } = \sqrt{(x_2 -x_1)^2 + (y_2- y_1)^2} [/tex]
where [tex](x_1, y_1)[/tex] and [tex](x_2, y_2)[/tex] are your coordinate points.

One of your coordinate points must be (-6, -10), let's make that our [tex](x_1, y_1)[/tex]. The other coordinate point is one of your answer choices.
Let's test each one:
Choice A (-3, -2):
[tex]\text{ Distance } = \sqrt{(x_2 -x_1)^2 + (y_2- y_1)^2}\\ = \sqrt{((-3) -(-6))^2 + ((-2)- (-10))^2} \\ = \sqrt{(3)^2 + (8)^2}\\ = \sqrt{9 + 64}\\ = \sqrt{73} [/tex]
This is not the right distance.

Choice B (3, 2):
[tex]\text{ Distance } = \sqrt{(x_2 -x_1)^2 + (y_2- y_1)^2}\\ = \sqrt{((3) -(-6))^2 + ((2)- (-10))^2} \\ = \sqrt{(9)^2 + (12)^2}\\ = \sqrt{81 + 144}\\ = \sqrt{225} \\ = 15[/tex]
This is the right distance!

Choice C (2, 3):
[tex]\text{ Distance } = \sqrt{(x_2 -x_1)^2 + (y_2- y_1)^2}\\ = \sqrt{((2) -(-6))^2 + ((3)- (-10))^2} \\ = \sqrt{(8)^2 + (13)^2}\\ = \sqrt{64 + 169}\\ = \sqrt{233} [/tex]
This is not the right distance.

Choice D (-2, -3):
[tex]\text{ Distance } = \sqrt{(x_2 -x_1)^2 + (y_2- y_1)^2}\\ = \sqrt{((-2) -(-6))^2 + ((-3)- (-10))^2} \\ = \sqrt{(4)^2 + (7)^2}\\ = \sqrt{16 + 49}\\ = \sqrt{65} [/tex]
This is not the right distance.

--------

Answer: B) (3, 2)